Vitamin D for the Treatment of Epilepsy: Basic Mechanisms, Animal Models and Clinical Trials - Pendo, Kevin; DeGiorgio, MD, Christopher M. (Frontiers in Neurology, 2016)
There is increasing evidence supporting dietary and alternative therapies for epilepsy, including the ketogenic diet, modified Atkins diet, and omega-3 fatty acids. Vitamin D3 is actively under investigation as a potential intervention for epilepsy. Vitamin D3 is fat-soluble steroid, which shows promise in animal models of epilepsy. Basic research has shed light on the possible mechanisms by which Vitamin D3 may reduce seizures, and animal data support the efficacy of Vitamin D3 in rat and mouse models of epilepsy. Very little clinical data exist to support the treatment of human epilepsy with Vitamin D3, but positive findings from preliminary clinical trials warrant larger Phase I and II clinical trials in order to more rigorously determine the potential therapeutic value of Vitamin D3 as a treatment for human epilepsy.